Sanksi Pidana terhadap Tenaga Medis yang Melakukan Pemalsuan Surat Keterangan Rapid Test Covid 19 - I Kadek Suar Putra Dana; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2021)
Current world conditions the outbreak of the Covid 19 virus that attacks humans around the world so that the Indonesian government takes a serious policy to tackle the spread of this virus by limiting areas this policy has resulted in crimes One of them is the crime of falsification of the covid test certificate 19 The formulation of the problem that can be raised is how to regulate the forgery of medical certificates in Indonesian criminal law? and what are the criminal sanctions for falsification of the Covid 19 rapid test certificate by medical personnel? This thesis research uses normative research type Letter forgery is regulated in KUHP articles 263 to article 267 besides that it is also regulated in article 7 of the medical code of ethics Sanctions for falsification of the COVID-19 rapid test certificate are subject to criminal sanctions and sanctions on medical code of ethics administrative sanctions If the doctor is proven to have committed forgery himself then the liability will be punished for a maximum of 4 (years) and administrative sanctions if it is carried out by the hospital the corporation will be subject to criminal three times the fine set against the individual.